Accompagner la gouvernance participative des eaux sousterraines pour une agriculture climatiquement intelligente en Afrique du Nord, Second scientific committee meeting, BRIDGE C4S aquifer co-management activity, Tunisia/Morocco, 10 July 2023 - Emeline Hassenforder (2023)
Managing water scarcity is a key priority to build future climate resilience of Maghreb agricultural systems. Groundwater-fed irrigation has been promoted to buffer drought risks and boost agricultural productivity but its overexploitation led rapidly to water use conflicts and questionable sustainability of the agricultural sector in many parts of water-stressed Morocco. This presentation of second scientific committee of ClimBeR activity led by BRIDGE consortium presents the progress of the development of aquifer comanagement decision support toolbox for agriculture and water stakeholders. Specifically examples of aquifer comanagement case studies; pilot site selection selection grid with 17 indicators; presentation of Wag-er role play to facilitate participatory strategy planning among local stakeholders.